Amylotheca cleofei sp. nov. (Loranthaceae), a new species and genus record for the Philippines - Tandang, Danilo N.; Galindon, John Michael M.; Lagunday, Noel E.; Coritico, Fulgent P.; Amoroso, Victor B.; Robinson, Alastair S. (Phytotaxa, 2021)
A new mistletoe species, Amylotheca cleofei, from Mount Hamiguitan Range Wildlife Sanctuary, Davao Oriental in the southern Philippines, is herein described and illustrated, representing a new species and genus record for the country. This species differs from other known Amylotheca species in terms of its distinctive reproductive and vegetative characters.